TINDAK TUTUR DIREKTIF BAHASA INDONESIA PADA POSTER KESEHATAN DI PUSKESMAS KOTA BANJARBARU - Eka Suryatin (Balai Bahasa Kalimatan Selatan, 2018)
The objective of this study is to (1) describe the types and characteristics of directive speech act marker on health posters at Community Health Center of Banjarbaru City and (2) describe the meaning of imperative sentences in health posters at Community Health Center of Banjarbaru City. This research is descriptive qualitative. The research data are in the form of written speech on the poster published by the Community Health Center of Banjarbaru City. The data sources are in the form of posters published or printed by the Community Health Center of Banjarbaru City. Data collection technique is taken by using documentation and writing techniques. The result shows that (1) the types of directive speech act found on health posters published by Community Health Center of the Banjarbaru City, are requestives with marker verb + kan, verb + i, and verb + lah, question with the marker when (kapan), prohibition with marker dilarang, requerement with the marker verb + kan, verb+ lah, and verb + i, and advisory with marker ayo and mari. (2) the forms of the imperative meaning on the health poster published by Community Health Center of the Banjarbaru City contain of command imperative, appeal imperative, urging imperative, inuitation imperative, and prohibition imperative.